The social science of QAnon: a new social and political phenomenon - Miller, Monica K. (Cambridge University Press, 2023)
"The unique conspiracy group called QAnon is growing in both membership and political power, and understanding this phenomenon is key to combating QAnon's negative effects on society. This book uses social science theory to explain the attraction and spread of the defining conspiracy movement of our times"--